FROM RESEARCH SKILLS TO RESEARCHER’S TRANSVERSAL COMPETENCE - Zogla, Irena (Education Reform: Education Content Research and Implementation Problems, 2021)
Different intellectual traditions imbedded in cultural and education settings and theoretical approaches to the understanding of skills, competencies, and transversal skills bring about many uncertainties in the conceptualization of research skills and competencies; together with the social demands towards the quality of graduates' competencies these draw heavily on the changing process of education, quality of educational provision, and interferes with the quality of the graduates’ achievements. Doctoral students usually face a large number of theoretical sources to analyze and make an appropriate theoretical underpinning of research; they also have to meet the uncertainties, experience incompetence that interferes with the allocated time and quality of investigation. While the shift to competence approach in education is thus more complex than many accounts suggest, it does have major implications for important aspects of studies and educators' work. This article aims to initiate doctoral students' thinking of the cultural background of different intellectual traditions in education and identify the most appropriate theoretical sources for their research. The article does not, however, provide final definitions or completed ideas. Based on the experience of the most popular projects in skills’development and theoretical analysis the published considerations might trigger new problems for doctoral students’ investigation and start their navigation in the enormous pool of literature. The article introduces some approaches to understanding and defining research skills, researcher’s competencies, and researcher’s transversal competencies, their structure, and experiences of measuring.